Sex addiction: in the eye of the beholder?: a comparison of 'sex addicts' versus 'non addicts' on measures of sexual behaviour, personality, categorical thinking, sexual attitudes, and religiosity - Mayes, Danielle (2015)
Introduction: ‘Sex addiction’ appears to have been largely accepted within clinical fields and popular culture. However, despite its 30 year history, the concept remains ill-defined and lacking in empirical data. Indeed, proponents of sex addiction continue to debate its terminology, definition, nosology, and aetiology, with a coherent model of the ‘disorder’ yet to be offered. An alternative account presented by the social constructionist model argues that the reason for this contention is because, rather than a pathological disorder, sex addiction represents a social construction. Those who argue from this perspective suggest that sex addiction has been created to pathologize sexualities which fail to promote dominant sexual norms. Whilst this argument appears convincing, it is not clear why some may be more influenced by these dominant sexual norms and thus pathologize their sexuality, whilst others do not consider their sexuality to be problematic. The answer to this may lie in certain individual differences, in particular, personality, thinking dispositions, sexual attitudes, and religiosity.